2023
DOI: 10.3390/s23052796
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Localization Efficiency and Accuracy in Wireless Sensor Networks

Abstract: Accuracy is the vital indicator in location estimation used in many scenarios, such as warehousing, tracking, monitoring, security surveillance, etc., in a wireless sensor network (WSN). The conventional range-free DV-Hop algorithm uses hop distance to estimate sensor node positions but has limitations in terms of accuracy. To address the issues of low accuracy and high energy consumption of DV-Hop-based localization in static WSNs, this paper proposes an enhanced DV-Hop algorithm for efficient and accurate lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…We are aware that a lower RMSE score corresponds to greater accuracy 25 . Research indicates that an increase in the number of anchor points (reference nodes) is associated with enhanced localization accuracy 25–27 . Adding more anchor points results in a greater quantity of data points and wider spatial coverage, facilitating the cross‐referencing of data and reducing measurement errors and outliers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware that a lower RMSE score corresponds to greater accuracy 25 . Research indicates that an increase in the number of anchor points (reference nodes) is associated with enhanced localization accuracy 25–27 . Adding more anchor points results in a greater quantity of data points and wider spatial coverage, facilitating the cross‐referencing of data and reducing measurement errors and outliers.…”
Section: Resultsmentioning
confidence: 99%
“…25 Research indicates that an increase in the number of anchor points (reference nodes) is associated with enhanced localization accuracy. [25][26][27] Adding more anchor points results in a greater quantity of data points and wider spatial coverage, facilitating the cross-referencing of data and reducing measurement errors and outliers. This increased number of anchor points enhances the localization algorithm's resilience to environmental changes.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…In Figures 10,11, and 12, the minimum, average, and maximum execution times of Amorphous-ALO and Amorphous-GWO are shown. From these figures, it can be observed that Amorphous-ALO is taking more time than Amorphous-GWO.…”
Section: Selection Of Suitable Optimization Algorithm For Amorphous B...mentioning
confidence: 99%
“…These dumb nodes don't know their position; to know it, they have to rely on anchors. The position identification of dumb nodes is essential for different position‐based applications 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…This algorithm exhibits excellent performance in reducing localization errors, and because of its low sensitivity to the number of nodes, the CMWN-DV-Hop (a = 10) algorithm can be applied to largescale wireless sensor networks [27]. Moreover, Fawad, M. et al proposed an improved DV-Hop algorithm, named the Hop-correction and energy-efficient DV-Hop (HCEDV-Hop) algorithm, to achieve efficient and accurate localization while reducing energy consumption [28]. To obtain accurate localization results, it is necessary to manage the topology structure within the DV-Hop algorithm effectively.…”
Section: Introductionmentioning
confidence: 99%